Keratinase production and biodegradation of polluted secondary chicken feather wastes by a newly isolated multi heavy metal tolerant bacterium-Alcaligenes sp. AQ05-001 - Yusuf I.; Ahmad S.A.; Phang L.Y.; Syed M.A.; Shamaan N.A.; Abdul Khalil K.; Dahalan F.A.; Shukor M.Y. (Academic Press, 2024)
Indexed by WOS/ Scopus